Teaching social studies : a methods book for methods teachers - Grant, S. G.; Lee, John; Swan, Kathy, 1969- (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
Teaching Social Studies: A Methods Book for Methods Teachers, features tasks designed to take preservice teachers deep into schools in general and into social studies education in particular. Organized around Joseph Schwab's commonplaces of education and recognizing the role of inquiry as a preferred pedagogy in social studies, the book offers a series of short chapters that highlight learners and learning, subject matter, teachers and teaching, and school context.The 42 chapters describe tasks that the authors assign to their methods students as either in-class or as outside-of-class assignments. The components of each chapter are:> Summary of the task> Description of the exercise (i.e., what students are to do, the necessary resources, the timeframe for completion, grading criteria)> Description of how students respond to the activity> Description of how the task fits into the overall course> List of readings and references> Appendix that supplements the task description.